Pemanfaatan Tumbuhan Obat Oleh Battra (Pengobat Tradisional) pada Tiga Dusun di Sekitar Hutan Tembawang Desa Sotok Kabupaten Sanggau - Irvan Gunawan; Yanieta Arbiastutie; Fathul Yusro; Yeni Mariani (Jurnal Serambi Engineering, 2022)
Sanggau Regency is still managing the Tembawang forest, one of which is in Sotok Village. The Tembawang forest in this village is overgrown with various fruit-producing trees and medicinal plants. Medicinal plants are used by traditional healers (battra) for their medicinal practices. The purpose of this study was to record and analyze the use of medicinal plants by Battra, who live in three sub-village around the Tembawang forest, Sotok Village, Sanggau Regency. This study used a survey method by conducting interviews with battra in three sub-villages: Sotok, Keladang I, and Keladang II. The results showed that battra utilized 69 species of medicinal plants consisting of 44 families, with the highest family being Zingiberaceae. The most utilization of medicinal plants by battra in Sotok, Keladang I, and Keladang II sub-village was found in herbaceous habitus (50.74%; 54%; 46.77%), plant parts in the form of leaves (59.42%; 53.85% and 60 .94%), processing and use by pounding (48.62%; 50%; 48.49%) and pasted (30.50%; 33.33%; 31.81%) as well as in the form of mixed ingredients (58.21%; 56%; 64.52%).